POTENSI, EFEKTIVITAS DAN KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KOTA YOGYAKARTA - Dita Dwi Agustina Darmanto; Indro Herry Mulyanto; Suratna Suratna (Jurnal Paradigma, 2019)
This study aims to determine the potential hotel tax that actually has inYogyakarta City, how far the level of hotel tax effectiveness and how much the hotel tax contribution in the City of Yogyakarta. This research is included in the type of quantitative descriptive research. The population in this study are all hotels in the city of Yogyakarta. The data used in this study are secondary data obtained from the Regional Finance and Assets Agency, Yogyakarta Central Statistics Agency. The sampling technique used is non probability sampling by means of purposive sampling based on selected criteria. The analysis technique uses the analysis of hotel tax potential calculations, analysis of hotel tax effectiveness calculations and analysis of hotel tax contribution calculations.The results of this study point out that the comparison between hotel tax  potential with the realization of hotel tax revenue within five years is from years 2011-2015 there is a big difference, with a potential hotel tax of Rp. 425,219,891,636 and realized hotel tax revenue of Rp. 335,529,045,226, then the local government lost the potential of Rp. 89,690,846,410, from the two hotel classifications in the city of Yogyakarta star hotels that have a greater proportion of potential than non-star hotels. The level of effectiveness shows that hotel tax revenue shows the average percentage is still below 100% with the criteria "Not Effective" so that it can be concluded that the realization ofhotel tax revenue in the city of Yogyakarta has not yet reached the maximum potential, while the level of hotel tax contribution to local revenue in The city of Yogyakarta in accordance with the targets set by the local government shows a percentage above 4% with the criterion "Very Contribute", so it can be concluded that the hotel tax contribution also contributes greatly to local original income in the city of Yogyakarta